One-to-one laptop programs: Is transformation occurring in mathematics teaching? - Blackley, Susan; Walker, Rebecca (Western Australian Institute for Educational Research Inc, 2015)
There is a body of research around the uptake of digital technologies in secondary schools, and a growing body of research specifically designed to investigate the use of one-to-one laptop programs. However this research focused on the initial uptake of the digital technology or initial implementation of a one-to-one (1:1) laptop policy. Given the expenditure of time and money associated with 1:1 laptop initiatives, investigation needs to be carried out to determine if the commitment has been worthwhile. This new study contributes to this body of research as it focused upon middle schools in which the 1:1laptop program has existed for over seven years; it sought to examine the evolution of teacher practice in mathematics education. Anonymous online surveys as well as semi-structured interviews with teachers were used to collect descriptive data. The data revealed that issues associated with the initial implementation of 1:1 laptop programs continued to be problematic, and little authentic integration of the technology had taken place in the pedagogical practices of the mathematics teachers.